Hierarchically structured metal carbides as conductive fillers in thermo‐responsive polymer nanocomposites for battery safety. (1st December 2022) - Li, Mingqian; Cai, Guorui; Holoubek, John; Yu, Kunpeng; Liu, Haodong; Sarwar, Shatila; Yan, Qizhang; Gao, Hongpeng; Zhang, Dawei; Zhou, Hanwei; Mukherjee, Partha P.; Lee, Suk-woo; et al.
Abstract: Integrating thermo-responsive polymer switching materials (TRPS) into lithium-ion batteries (LIBs) has been recognized as one of the most effective strategies to prevent thermal runaway under various abuse scenarios. However, the current methods to obtain TRPS cannot satisfy different practical applications. Herein, we develop a versatile strategy for the preparation of various metal carbides ( e.g., tungsten carbide, molybdenum carbide) with controllable hierarchical structure that is featured with surface protrusion structure, which is critical for high conductivity and rapid thermal response. Systematic studies of the phase and morphology evolutions by advanced characterizations illustrate that the reducing agent and reduction rate are critical for developing the specific morphology. By using the above-mentioned carbides as the conductive fillers of TRPS, the resulting TRPS with a specially controlled shape exhibits over 5 order of conductivity improvement compared with common carbides with particulate morphology, in addition to reversible shutdown performance and effective thermal abuse protections toward safe LIB operation. Graphical Abstract: A universal 2-step method of metallic carbides synthesis is designed to obtain tungsten carbides with spiky spherical morphology. Thermal-responsive polymer composites embedded with as-synthesized tungsten carbide exhibit orders of magnitude improvement of conductivity and secure effective safety protection of Li-ion batteries against overheating and prevent potential thermal runaway. ga1 Highlights: A universal synthetic route to obtain metallic carbides with any desired hierarchically structured was developed. Spherical-spiky tungsten carbides and hollow sphere molybdenum carbides were synthesized successfully. Separated reduction-carbonization process and uniform carbon coating layer benefit the maintenance of the architecture. Thermo-responsive polymer switching materials were fabricated to provide thermal abuse protection to NCMǁGr full cells. 5 orders of magnitudes improvement on conductivity of thermo-responsive polymer switching materials is achieved.